Deradikalisasi Pendidikan Sebagai Antitesis Penyimpangan Paradigma dan Tujuan Pendidikan Nasional - Widhiya Ninsiana (Tarbawiyah Jurnal Ilmiah Pendidikan, 2017)
The sacred mission of education as stipulated in the motto of Indonesian Higher Education, which is to implement tridharma concept (education, research, and community service). However, looking at the current reality, it will be difficult for us to see our PT being able to succesfully implement the tridharma. This paper attempts to criticize our higher education which has unwittingly long ago developed into an agent of capitalism that perpetuates the system of capitalism in the practice of administration and policy of the higher education in Indonesia. Radicalism in education has been a potential futuristic threat to realize the quality of education. Radicalism may arise at any time, from anywhere and can be carried out by anyone, including by higher education institutions and government through various policy issued as Permenistek Dikti. Therefore radicalism needs to be fully integrated and comprehensively undertaken through constructive steps (deradicalisation) so that it can perform synergy neatly and precisely and relies on the paradigm and purpose of education itself.